93 10-year prognosis of adolescent knee pain – a prospective population-based cohort study. (25th January 2023) - Rathleff, Michael Skovdal; Brøndum, Pernille; Roos, Eva; Sørensen, Line Bay; Larsen, Jesper Bie; Olesen, Jens Lykkegaard; Chang, Alison; Holden, Sinead
Abstract : Introduction: Knee pain affects one in three adolescents. No studies have prospectively evaluated the long-term impact of knee pain in later life. The Adolescent Pain in Aalborg (APA 2011) cohort included a population-based sample of 504 adolescents aged 15–19 years with knee pain. This study aims to describe the preliminary findings from selected outcomes after 10-years. Materials and Methods: This population-based cohort study included the following outcomes at the 10 year follow-up: Knee injury and Osteoarthritis Outcome Score (KOOS), pain intensity, pain frequency, other pain locations, health-related quality of life, weekly sports participation, physical activity (International Physical Activity Questionnaire), sleep quality, healthcare consultations, diagnoses, and treatments or knee pain, pain-killer usage, and impact on the choice of job/career. Results: 53.8% of participants with knee pain at baseline have responded by 12/10/2022; (n=271, mean age=28.1±1.2 years, BMI=25.4±5.0 kg/m2, 71% women). Final results are expected in 2023. 38.0% experienced knee pain during the last week, with 33% reporting pain at least several times per week. Average KOOS Sport/recreation scores were 61±22, and KOOS QoL were 61±20 for those who continued to experience knee pain, and 86±15 and 84±15, respectively, for those recovered from knee pain. 60.0% with ongoing knee pain report difficulties sleeping. Conclusion: Preliminary findings from this first prospective population-based study examining the 10-year prognosis of knee pain from adolescence into adulthood indicate that knee pain persists after 10-years in nearly 40% of adolescents and is associated with very low KOOS scores compared to those recovered from knee pain.